Determination of NUDT15 variants by targeted sequencing can identify compound heterozygosity in pediatric acute lymphoblastic leukemia patients - Yu, Chih-Hsiang (Sci Rep, 2020)
Mercaptopurine intolerance is an adverse effect of mercaptopurine administration in pediatric acute lymphoblastic leukemia. Recently, NUDT15 variants were identified as a major determinant of mercaptopurine intolerance. Two NUDT15 variants, c.36_37insGGAGTC and c.415C > T, are located on exons 1 and 3, respectively. Patients with heterozygous c.36_37insGGAGTC and c.415C > T can be either compound heterozygous with two variants on different alleles or heterozygous with both variants on the same allele. Because patients with biallelic NUDT15 variants are extremely sensitive to mercaptopurine, clinical identification of NUDT15 diplotype would be advantageous. A cohort of 37 patients with c.36_37insGGAGTC and c.415C > T NUDT15 variants were selected for haplotyping by targeted sequencing. NUDT15 complementary DNA was amplified and sequenced by 300-bp paired-end sequencing on Illumina MiSeq. Of the 37 patients carrying NUDT15 variants, 35 had heterozygous NUDT15*1/*2 variants and two had compound heterozygous NUDT15*3/*6 and NUDT15*2/*7 variants. These two patients with compound heterozygous variants could only tolerate low doses of mercaptopurine, similar to patients with homozygous NUDT15 variants. Targeted sequencing of NUDT15 cDNA can be used to determine NUDT15 diplotype and identify patients with compound heterozygous NUDT15 variants.